2007
DOI: 10.1128/aac.00969-06
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole Prophylaxis in Experimental Systemic Zygomycosis

Abstract: Three isolates of zygomycetes belonging to two different genera (Rhizopus oryzae and Absidia corymbifera) were used to produce a systemic infection in neutropenic mice. On days ؊2 and ؊1 and at 2 h prior to infection, the mice received either posaconazole (POS) at doses ranging from 20 to 80 mg/kg of body weight/day or amphotericin B (AMB) at 1 mg/kg/day. Antifungal drug efficacy was assessed by determination of the prolongation of survival, determination of the percentage of infected organs (brain, lung, sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 12 publications
(18 reference statements)
1
26
0
1
Order By: Relevance
“…In an animal infection model, PSC showed poor efficacy against a strain of R. oryzae (4). Similarly, prophylactic administration of PSC to neutropenic mice prolonged survival but did not reduce the tissue burden in a disseminated infection caused by R. oryzae (2). The current study partly confirmed these results.…”
supporting
confidence: 80%
“…In an animal infection model, PSC showed poor efficacy against a strain of R. oryzae (4). Similarly, prophylactic administration of PSC to neutropenic mice prolonged survival but did not reduce the tissue burden in a disseminated infection caused by R. oryzae (2). The current study partly confirmed these results.…”
supporting
confidence: 80%
“…68 A few animal studies have been conducted to explore the in vivo efficacy of posaconazole in screening models of disseminated mucormycosis that used survival and/or fungal tissue burden as end points. [69][70][71][72][73] Posaconazole prolonged the survival and reduced tissue burden in neutropenic mice with disseminated Mucor infection and was as effective as standard AmB at the highest dose level. 69 In non-immunocompromised mice, no beneficial effects were observed against R. oryzae, while partial activity was shown against Lichtheimia corymbifera and dose-dependent activity against Rhizopus microsporus.…”
Section: Posaconazolementioning
confidence: 99%
“…In both of these last two studies, AmB significantly prolonged the survival of mice infected with all isolates. 70,72 In a further neutropenic murine model of disseminated R.oryzae mucormycosis, posaconazole had modest, but significant effects on survival that were statistically inferior to AmB at 0.8 mg/kg/day. 73 Finally, in diabetic ketoacidotic or neutropenic mice with disseminated mucormycosis caused by R. oryzae, posaconazole monotherapy did not improve survival or reduce fungal burden as compared to placebo while L-AmB was effective.…”
Section: Posaconazolementioning
confidence: 99%
“…Considering the low frequency of infection with this organism and the difficulty in obtaining statistically significant data regarding the efficacies of antifungal agents, animal models have proved very useful for this purpose. Previous animal studies evaluating the efficacy of PSC against zygomycetes have included only one or two strains of R. oryzae (3,4,9,19). In the study described here, we have tested a panel of 50 clinical isolates of R. oryzae and, after determining their in vitro susceptibilities to PSC by different methods, have selected a subset of strains with various degrees of susceptibility to evaluate the efficacy of PSC in a murine model of infection.…”
mentioning
confidence: 99%